Developmental toxicity evaluation of sub-CO2 extract of Phaleria macrocarpa fruit flesh in Danio rerio embryo - Mia, Md. Abdur Rashid; Sarker, Md. Zaidul Islam; Ferdosh, Sahena; Ahmed, Qamar Uddin; Uddin, A.B.M Helal; Abul Kalam, Azad (2020)
Phaleria macrocarpa, traditionally known as Mahkota dewa, is a therapeutic herb that is being used for anti-obesity, antidiabetic, antioxidant, and anticancer activities. To perform animal study and administration dose measurement, to identify the safety profile level of plant extract is very important. The main aim of this study is to evaluate the toxicity level of the subcritical carbon dioxide (Sub-CO2) extract in Danio-rerio embryo. Fruit was chosen and subsequently extracted using Sub-CO2 technique. The Box-Behnken Design (BBD) was used to optimize and examine the effect of independent variables of Sub-CO2 such as temperature (27-29˚C), pressure (6.8-7.0 MPa) and concentration of co-solvent. The toxicity study of Sub-CO2 extracts was examined by using Danio-rerio embryo at 0 to 96 hpf. The protocol of toxicity study on zebrafish embryo was adapted according to OECD guideline section 212.Sub-CO2 extract of P. macrocarpa was applied to screen the toxicity level at the dose of 100 – 1000 µg/ml. The tested report showed considerable (>90%) mortality and delay in hatching at higher concentrations of 1000 µg/ml. Overall, there was a mild toxicity observed in experimental embryo development when compared to control. However, the LC50 value was obtained at the concentration of 841.39 µg/ml. Toxicity study of different ratio of Sub-CO2 extracts from P. macrocarpaa showed mild toxic effects on zebrafish embryos, however, the extract comparatively safe for normal embryonic development at the range from 50 to 841.39 µg/ml. This finding could help to predetermine the dosage P. macrocarpa fruit for further in vivo study